2024
DOI: 10.11609/jott.8700.16.2.24730-24736
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring observations of the southernmost breeding population of Long-billed Vultures Gyps indicus (Scopoli, 1786) (Aves: Acciptriformes: Accipitridae) in the Nilgiri Biosphere Reserve, India

S. Manigandan,
H. Byju,
P. Kannan

Abstract: The Long-billed Vulture (LBV) population was systematically monitored across four nesting colonies in the Nilgiri Biosphere Reserve (NBR) throughout three extended breeding seasons. Breeding success rates between years ranged from 83.33% in 2018–2019 and 62.5% in 2020–2021. Nesting was monitored at the cliff sites, consistent with prior research. Overall population fluctuations were minimal, varying between 21 individuals in 2020–2021, 17 individuals in 2018–2019, and 16 individuals in 2019–2020. There was an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Bhusal et al (2019) and Galligan et al (2019) have previously reported an increase in the vulture population following the ban on diclofenac in 2006. Even though in NBR, vultures faced new threats as forest fire and illegal tourism (Manigandan et al 2024), our findings suggest that the population appears to be relatively stable (Manigandan et al 2023a).…”
mentioning
confidence: 70%
“…Bhusal et al (2019) and Galligan et al (2019) have previously reported an increase in the vulture population following the ban on diclofenac in 2006. Even though in NBR, vultures faced new threats as forest fire and illegal tourism (Manigandan et al 2024), our findings suggest that the population appears to be relatively stable (Manigandan et al 2023a).…”
mentioning
confidence: 70%